Embrace the Sea, Saving the Community's Economy Akar Island, Setokok Village, Batam - Nur Effendi Anwar; Mursal Mursal; Andi Mulyadi; Diana Titik Windayati (LPPM STIE Krakatau, 2025)
Purpose: The community’s efforts to develop the family economy began when they realized that rengkam seaweed could be utilized to increase household income, which became the author's motivation to conduct this research. Methodology/approach:This study employed a quantitative method involving questionnaire-based data collection and statistical analysis for hypothesis testing. It aims to establish cause-and-effect relationships between variables and gain a deeper understanding of social situations. Results/findings: The analysis confirms that all indicators are valid and significant, with each variable showing a significant influence. The model's Goodness of Fit meets most criteria, allowing it to be considered good, though improvements are still possible. Conclusions: Empowering communities through knowledge and skills related to local resources like rengkam seaweed can significantly boost family economic growth. The proposed model shows strong structural validity and offers practical implications for economic development programs Limitations: This study focuses on one community and rengkam seaweed for economic empowerment, making the findings less applicable to other regions or seaweed types. The use of a quantitative method may overlook socio-cultural aspects, so future research should consider a mixed-methods approach for deeper insights.. Contribution: This study highlights the potential of rengkam seaweed in boosting household income and shows that motivation, education, and skills play key roles in family economic growth. The findings can guide targeted empowerment programs using local resources.